STRATEGI PENGEMBANGAN SALAK NGLUMUT DI KABUPATEN MAGELANG - Ardiyanto Ardiyanto; Dwidjono Hadi Darwanto; Sutrilah Sutrilah (Agro Ekonomi, 2008)
This research aims: (1) to identify the income difference between Salak Pondoh and Salak Nglumut farmers; and (2) to analyze the external (opportunity and threat) and internal factor (weakness and strength) for developing Salak Nglumut in Magelang district. The sample was chosen by purposive sampling, i.e. Srumbung and Salam sub district. The data was collected by interviewing 60 respondents; that were policy makers in Magelang district, Salak Nglumut farmers, Salak Pondoh farmers, and salak consumers. The t-test shows that the income of Salak Pondoh farmers is lower than the income of Salak Nglumut farmers. The result of SWOT analysis is located in quadrant 1. This means that Salak Nglumut is a profitable farm as it has higher opportunity and strength. In this condition, Salak Nglumut farmers should apply aggressive Growth Oriented Strategy. The recommended growth strategy in developing Salak Nglumut is using it as appropriate location for agro-tourism, marketing salak in provincialroads, developing special market for salak which close to tourism. objects,increasing funding sources for salak farmers, developing infrastructure toSalak Nglumut agro-tourism location, or also developing salak homeindustry that more longer resistant and practically.